Effect of local gentamicin–collagen on perineal wound complications and cancer recurrence after abdominoperineal resection: a multicentre randomized controlled trial. (27th February 2013) - Collin, Å.; Gustafsson, U.‐M.; Smedh, K.; Påhlman, L.; Graf, W.; Folkesson, J.
Abstract Aim Perineal wound sepsis is a common problem after abdominoperineal resection of the rectum (APR), with a reported incidence of 10–15% in previously non‐irradiated patients, 20–30% in patients given preoperative radiation and 50% among patients submitted to preoperative radiation combined with chemotherapy. The local application of gentamicin–collagen was evaluated to determine whether its use in the perineal wound reduced risk complications and had an effect on cancer recurrence. Method In this prospective multicentre (seven hospitals) randomized controlled trial, 102 patients undergoing APR due to cancer or benign disease were randomized into two groups including surgery with gentamicin–collagen (GS+, n = 52) or surgery without gentamicin–collagen (GS−, n = 50). Patients were followed at 7, 30 and 90 days and at 1 and 5 years. Results There were no statistically significant differences between the two groups regarding perineal wound complications, infectious or non‐infectious, or cancer recurrence. Conclusion There was no statistically significant effect on perineal wound complications or cancer recurrence following the local administration of gentamicin–collagen during APR.